New Insights From Pre-Columbian Land Use and Fire Management in Amazonian Dark Earth Forests - Maezumi, S. Yoshi; Robinson, Mark; de Souza, Jonas; Urrego, Dunia H.; Schaan, Denise; Alves, Daiana; Iriarte, Jose (Frontiers in Ecology and Evolution, 2018)
Anthropogenic climate change driven by increased carbon emissions is leading to more severe fire seasons and increasing the frequency of mega-fires in the Amazon. This has the potential to convert Amazon forests from net carbon sinks to net carbon sources. Although modern human influence over the Earth is substantial, debate remains over when humans began to dominate Earth’s natural systems. To date, little is known about the history of human land use in key regions like the Amazon. Here, we examine the history of human occupation from a 8,500 year-old sediment core record from Lake Caranã (LC) in the eastern Amazon. The onset of pre-Columbian activity at LC ( 4,500 cal yr B.P.) is associated with the beginning of fire management and crop cultivation, later followed by the formation of Amazonian Dark Earth soils (ADEs) 2,000 cal yr B.P. Selective forest enrichment of edible plants and low-severity fire activity altered the composition and structure of forests growing on ADEs (ADE forests) making them more drought susceptible and fire-prone. Following European colonization (1661 A.D.), the Amazon rubber boom (mid-1800s to 1920 A.D.) is associated with record-low fire activity despite drier regional climate, indicating fire exclusion. The formation of FLONA Reserve in 1974 A.D. is accompanied by the relocation of traditional populations and a fire suppression policy. Despite suppression efforts, biomass burning and fire severity in the past decade is higher than any other period in the record. This is attributed to combined climate and human factors which create optimal conditions for mega-fires in ADE forests and threatens to transform the Amazon from a net carbon sink to a net carbon source. To help mitigate the occurrence of mega-fires, a fire management policy reducing fire-use and careful fire management for farming may help to reduce fuel loads and the occurrence of mega-fires in fire-prone ADE forests. As both natural and anthropogenic pressures are projected to increase in the Amazon, this study provides valuable insights into the legacy of past human land use on modern ADE forest composition, structure, and flammability that can inform ecological benchmarks and future management efforts in the eastern Amazon.